Synthesis of Benzopyran Linked Pyrrolo[2,1-c][1,4]benzodiazepines as DNA-Binding and Potential Anticancer Agents - Kamal, Ahmed; Rajender; Kashi Reddy, Methuku; Santhosh Reddy, Vangala; Bharath Kumar, Gajjela (Medicinal Chemistry, 2013)
A series of twelve benzopyran linked pyrrolo[2,1-c][1,4]benzodiazepines (PBDs) have been synthesized. They exhibit significant DNA-binding activity and excellent cytotoxic activity against various human cancer cell lines.
Keywords: DNA-Binding affinity